Project - based learning to develop speaking skill. - Taipe Vergara, Diana Karina (2023)
The general objective of this research is to develop oral skills by applying the Project-Based Learning (ABP) methodology at the Language Center of the Technical University of Cotopaxi. In this study, a qualitative approach was used to analyze and interpret the data in order to address the concern identified in the Language Center. The type of research is action research, this was an important component that allowed the researcher to identify the problem and then commit to the process of development of the target language through its four phases: plan, act, observe and reflect and thus contribute with its improvement.